Preoperative risk assessment for postoperative pancreatic fistula (POPF): Image-based calculation of duct-to-parenchyma (D/P) ratio and an Alignment of Duct and Mucosa (ADAM) anastomosis may lead to a low POPF rate—results from 386 patients - Krueger, Colin M.; Langheinrich, Melanie; Biesel, Esther A.; Kundel, Lena; Krueger, Karsten; Adam, Ulrich; Riediger, Hartwig (Frontiers in Surgery, 2022)
Background Postoperative pancreatic fistula (POPF) is the most critical complication after pancreatoduodenectomy (PD). Preoperative identification of high-risk patients and optimal pancreatic reconstruction technique can be a way to reduce postoperative complications. Methods A series of 386 patients underwent PD over a 10-year period (2009-2019). On routinely performed preoperative computed tomography (CT) images, the ventro-dorsal diameters of duct (D) and parenchyma (P) were measured in the cutting plane at the superior mesenteric vein. Then, the ratio of both values was calculated (D/P ratio) Double-layer pancreatojejunostomy with alignment of duct and mucosa (ADAM) by two monofilament threads (MFT) was performed in 359 patients and pancreatogastrostomy (PG) in 27 patients.. The incidence of POPF was diagnosed according to the International Study Group for Pancreatic Fistula criteria. Results The overall rate of POPF was 21 % (n=80), and the rate of clinically relevant type B/C fistulas 6.5% (n=25). A D/P ratio of <0.2 was significantly associated with type B/C fistula (11%, p<0.01). In low-risk patients (D/P ratio >0.2), type B/C fistula occurred only in 2%, and in high-risk patients (D/P ratio <0.2) in 9%. ADAM anastomosis was performed safely by two different surgeons. A PG anastomosis had double-digit POPF rates in all groups. Conclusion Preoperative CT imaging with D/P measurement may predict the risk of POPF development. A cut off D/P ratio of <0.2 was significantly associated with clinical relevant POPF. ADAM anastomosis may be an option for pancreatojejunostomy. However, preoperative knowledge of the D/P ratio could guide decision-making for primary pancreatectomy when pancreatic reconstruction is critical.